Capabilities and Problems of the Credit-Module System - Rashidova Nilufar; Sayfullayeva G. I. (Academia One Publishing, 2023)
Organization of educational processes in a credit-modular system dramatically increases the effectiveness of the educational process. First of all, giving students the opportunity to choose will strengthen their aspirations for knowledge. Experiences gained over the past period show that allowing a student to choose a teacher activates them, they begin to discuss with upper-level students by quickly getting in touch. The references to the presented science teachers are carefully studied, and the processes of enrolling in the subjects of teachers become more and more individual. In fact, an academic group of traditional form is not a suitable unit for a credit-module system. This factor was evident in the experiments carried out in the past period on the formation of personal educational trajectories of students
Keywords: credit-module system; education; process